Internet connectivity disruption in Spain (Spain) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Spain. Data sourced from IODA.
Network Disruption Incident ID: ES-2026-0006. Severity: critical. Confidence: 65%